Preparation and properties of lead free bismuth sodium titanate-bismuth zinc titanate ceramics - Muanghlua R. (2014)
Lead-free piezoelectric ceramics based on (1-x)Bi1/2Na1/2TiO3 - x Bi(Zn1/2 Ti1/2)O3 (x = 0.0, 0.02, 0.04, 0.06, 0.08, 0.10, 0.20, 0.30, 0.40, and 0.5) were obtained via solid-state processing techniques. The influence of BZT addition on BNT characteristics, sintering, microstructure and properties was investigated. A single perovskite phase with rhombohedral symmetry was obtained for Bi(Zn1/2Ti1/2)O3 substitutions of up to 10 mole%. A small amount of BZT was effective for improving both sintering behavior and dielectric properties of BNT ceramics. Optimized dielectric properties were obtained for samples with a maximum density of ρ = 98.3% for the composition, x = 0.1. Copyright © Taylor & Francis Group, LLC.